Renaming in Paul’s Churches: The Case of Crispus-Sosthenes Revisited - Fellows, Richard (Tyndale bulletin, 2005)
If Crispus was Sosthenes we no longer need to hypothesise that there were two Sosthenes (Acts 18:17 and 1 Cor. 1:1) or two ἀρχισυνάγωγοι (synagogue rulers) who became believers (Acts 18:8 and 18:17; 1 Cor. 1:1). The idea that Crispus was re-named ‘Sosthenes’ creates a remarkably consistent picture of the individual. Luke presents him as a synagogue ruler who caused many others to become Christians (Acts 18:8), and tells us that the Jews singled him out for a beating (Acts 18:17). The authority that his name carried among the believers in Corinth explains why Paul included him as a co-sender (1 Cor. 1:1). Paul named him ‘Sosthenes’, meaning ‘saving strength’, because, through his power and influence, he secured the viability of the fledgling Christian community in Corinth. This style of naming is in keeping with other examples.